"I've been always strong to conquer any suffering:" challenges and resilience of Chinese American dementia caregivers in a life course perspective. (2nd September 2021) - Liu, Jinyu; Lou, Yifan; Wu, Bei; Mui, Ada Chan Yuk-Sim
Abstract: Objectives: This study investigated the resilience of a growing but largely underserved and understudied population—Chinese American dementia caregivers, whose experience is embedded in their development throughout the life span, process of migration, and sociocultural contexts. Method: Narrative data were collected from in-depth interviews with 27 Chinese caregivers in New York City. Based on the hybrid grounded theory model, a three-steps coding procedure was implemented to identify themes emerged from the data. Results: 16 themes emerged from the data and fit two categories, challenge and resilience, in each of the four principles—time and place, timing in lives, linked lives, and agency—of the developmental life course perspective. Physical and emotional exhaustion is the challenge theme that was the most frequently mentioned followed by limited knowledge of dementia, navigating the U.S. health care system, and limited time for self-development. Three aspects of resilience—sense of mastery, access to formal and informal support, and commitment to care—were salient among the Chinese American caregivers. Conclusion: This study shed important light on the multifaceted challenges and resilience of Chinese American caregivers. The findings indicate the necessity of developing culturally meaningful services for immigrant caregivers to address their complex challenges and improve their multifaceted resilience.